Highly stable surface modification of hypercrosslinked monolithic capillary columns and their application in hydrophilic interaction chromatography. Issue 17 (19th July 2013) - Škeříková, Veronika; Urban, Jiří; Svec, Frantisek
<x xml:space="preserve">Abstract</x> A two‐step surface modification of poly(styrene‐co‐vinylbenzyl chloride‐co‐divinylbenzene) monolithic stationary phases, including hypercrosslinking and thermally initiated surface grafting of [2‐(methacryloyloxy)ethyl]dimethyl(3‐sulfopropyl)ammonium hydroxide, has been used to prepare capillary columns for the isocratic separation of small polar compounds in hydrophilic interaction chromatography (HILIC). The prepared monolithic columns provided a dual retention mechanism, combining RP and hydrophilic interaction chromatography, controlled by the composition of the mobile phase. By the optimization of the surface grafting reaction using response surface methodology, we have found that the grafting time is the main synergistic effect controlling the retention of polar compounds in HILIC. The prepared monolithic columns achieved long column lifetimes and did not lose their separation power following >10 000 injections. Finally, hypercrosslinked columns have been used in the 1‐ and 2D LC of phenolic compounds.